Self- Efficacy and Self- Knowledge as Predictors of Workers’ Job Performance in Food and Beverage Industries in the South-West, Nigeria - Fejoh, Johnson; Boyede, Michael Ayodeji; Momoh, Agbomehre Medinat (NIU Journal of Humanities, 2018)
This study investigated self- efficacy and self- knowledge as predictors of workers’ job performance in food and beverage industries in South-West, Nigeria. Poor job performance in Nigerian Industries has been partially attributed to low workers’ self-efficacy and poor self-knowledge. The descriptive survey design was adopted. Four factories were purposively selected from three states in South-West, Nigeria (Lagos, Ogun and Oyo States). Proportionate random sampling techniques were used in selecting 1,820 junior and supervisory cadre workers in Nestle Plc. (369), Coca-Cola Plc. (392), Cadbury Plc. (443) and Nigeria Breweries Plc. (616). The three research instruments used were: Workers’ self-efficacy (r=0.81), Workers self-knowledge (r=0.78) and Workers’ performance rating (r=0.72) scales. Quantitative data were analyzed using Pearson Product Moment Correlation, Multiple Regression at 0.05 level of significance. Findings show that there were significant relationships between workers’ job performance and self-efficacy (r=.56) and self-knowledge (r=.54) respectively. Self-efficacy and self-knowledge, jointly predict workers’ job performance (F (4, 1815) = 491.05) accounting for 52.0% of its variance. Self-efficacy (B=.10), self-knowledge (B=.11) had relative predictive weights on workers’ job performance. Inadequate knowledge and training of the supervisors led to a mismatch between workers’ self-efficacy and self-knowledge thereby reducing workers’ job performance. High self-efficacy and good self-knowledge have influence on workers job performance. Based on the findings, employers of labour should provide work environment that would enhance and promote the development of these factors among the workers. Keywords:     Self-efficacy, Self-knowledge, Workers’ Job Performance, Food and Beverage Industries, South-West, Nigeria.